\(Δ^m\)-Statistical Convergence in Intuitionistic Fuzzy Metric Spaces - Or, Aykut; Antal, Reena; Özcan, Ahmet (Communications in Mathematics and Applications, 2024)
In this study, we propound statistical convergence and statistical Cauchy sequences for generalized difference sequences in intuitionistic fuzzy metric spaces and establish a Cauchy convergence criterion for this novel notion of convergence. Furthermore, we offer an exhaustive characterization of the mentioned notions of generalized difference sequences. Lastly, we discuss whether the phenomena should be further investigated.